1971
DOI: 10.1055/s-0028-1099631
|View full text |Cite
|
Sign up to set email alerts
|

DIE FLAVONOLGLYCOSIDE VONEUPHORBIA MYRSINITIS

Abstract: Ihre Isolierung und Identifizierung Mitteilung iiber die Flavonoide einheimischer EuphorbiaceenUV-Maxima der Glycoside und Aglyca aus E. rnyrsinitis ohne und rnit ionisierenden und komplexbildenden Zusatzen in Methanol (Mabry und Mitarb. (1970) Myr 1 Clycosid Aglycon MeOH 265,296 sh, 315 sh, 344 253 sh, 266, 294 sh, 322 sh, 367 NaOMe 273,325,389 281,316 sh, 422 (Zers.) AICI, 273,304,351,395 260 sh, 270,307,358,424 AICI,/HCI 274,301,351,395 256 sh, 269,305 sh, 357,417 NaOAc 273,318 sh, 382 276,307,391 NaOAc/H,B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Ther elative configuration of 1 wase stablished mainly usingi nformation of the NOESY spectrum, and by comparison of its spectroscopic data with those of other jatrophane diterpenes [12]. Overhauser correlation of HÀC(13)/HÀC (11) indicated that HÀC (11) Compound 3 was identified as isoterracinolide B, isolated previously from Euphorbia terracina [13], but described here for the first time to be present in E. exigua as well. Overhauser correlation of HÀC(13)/HÀC (11) indicated that HÀC (11) Compound 3 was identified as isoterracinolide B, isolated previously from Euphorbia terracina [13], but described here for the first time to be present in E. exigua as well.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Ther elative configuration of 1 wase stablished mainly usingi nformation of the NOESY spectrum, and by comparison of its spectroscopic data with those of other jatrophane diterpenes [12]. Overhauser correlation of HÀC(13)/HÀC (11) indicated that HÀC (11) Compound 3 was identified as isoterracinolide B, isolated previously from Euphorbia terracina [13], but described here for the first time to be present in E. exigua as well. Overhauser correlation of HÀC(13)/HÀC (11) indicated that HÀC (11) Compound 3 was identified as isoterracinolide B, isolated previously from Euphorbia terracina [13], but described here for the first time to be present in E. exigua as well.…”
mentioning
confidence: 71%
“…Euphorbia exigua L. is an annual weed with southern-temperate distribution, whose diterpene constituentsh ave not been reported previously.E arlier, Dumkow and Pohl isolated four flavonol glycosides fromt he herbs [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 tion 1) and the filtrate was allowed to cool to room temperature. A greenish amorphous material (4.5 8.)…”
mentioning
confidence: 99%